2014
DOI: 10.4067/s0718-58392014000200007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and phylogenetic analysis of honey bee viruses in the Biobío Region of Chile and their association with other honey bee pathogens

Abstract: Different episodes of mortalities of honey bee (Apis mellifera L.) colonies have been associated with the presence of honey bee pathogens. Since the Biobío Region has among the highest number of apiaries in Chile, the aim of the present study was to identify viruses in the Region affecting honey bees, evaluate their relation to other pathogens, and conduct a phylogenetic analysis. Pupae and adult bees were collected from 60 apiaries of Apis mellifera L. in the Biobío Region over 2 yr. RNA viruses were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
0
18
1
Order By: Relevance
“…Later, these same viruses were detected in Brazil with the exception of CBPV (Teixeira et al 2008;Freiberg et al 2012), and in Argentina (Reynaldi et al 2010;Brasesco et al 2013), and in Chile, with the exception of CBPV (Barriga et al 2012;Rodríguez et al 2012Rodríguez et al , 2014. RNA viruses were detected in colonies from apiaries with antecedents of colony losses and in apiaries without clinical symptoms of diseases as well.…”
Section: Rna Virusesmentioning
confidence: 85%
See 2 more Smart Citations
“…Later, these same viruses were detected in Brazil with the exception of CBPV (Teixeira et al 2008;Freiberg et al 2012), and in Argentina (Reynaldi et al 2010;Brasesco et al 2013), and in Chile, with the exception of CBPV (Barriga et al 2012;Rodríguez et al 2012Rodríguez et al , 2014. RNA viruses were detected in colonies from apiaries with antecedents of colony losses and in apiaries without clinical symptoms of diseases as well.…”
Section: Rna Virusesmentioning
confidence: 85%
“…However, as a result from the sanitary vigilance from the National Sanitary Service (SAG), an average prevalence of 8 % was determined in 2010 in the country (SAG 2015). In a more recent analysis with a major sample size, some areas with more than a 20 % prevalence were found (especially in the case of unprofessional beekeepers), while other areas obtained negative values (Aldea et al 2013b;Rodríguez et al 2014). The relevance of the tracheal mite in Chile is unclear, as well as if the interaction between V. destructor and A. woodi is responsible, at least in part, for the high number of mortalities caused by Varroa (Aldea et al 2013b).…”
Section: Acarapisosismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, N. ceranae does not appear to have a strong within-host advantage for either infectivity or spore growth, suggesting that direct competition in worker bee mid-guts is not responsible for its apparent replacement of N. apis (Milbrath et al, 2015). In another recent report in Chile, N. apis has been detected to have a low prevalence (3%) by molecular tools (Rodríguez et al, 2014) and in some cases, N. apis has not been detected at all (Bravo et al, 2014). Considering that the use of molecular tools for identifying Nosema species is relatively recent, previous reports of N. apis infections, prior to 2009 in Chile, were carried out with light microscopy only; therefore, there is a possibility that morphological identifications mistakenly identified N. ceranae as N. apis.…”
Section: Resultsmentioning
confidence: 97%
“…Nosema has been detected in 10% of colonies in the Azapa valley, Arica and Parinacota Districts (Huaiquil et al 2009) Rodríguez et al (2014) detected N. ceranae in 18% of hives analysed in the Biobío District out of a total of 180 colonies sampled. It is suggested that N. ceranae may be the real cause of nosemosis in A. mellifera in South America.…”
Section: Nosema Ceranae In Chilementioning
confidence: 99%